Graduated Capacity for Responsibility of Children Under Twelve in the Indonesian Juvenile Criminal Justice System: : A Mental-Capacity-Based Reformulation - Syakhiya Aprilia Wardani; Milda Istiqomah; Faizin Sulistio (IJBLE Scientific Publications Community Inc., 2026)
Indonesian juvenile criminal law treats children below the age of twelve as outside the category of children in conflict with the law and restricts the available legal response to non-penal measures. Article 21 of Law No. 11 of 2012 on the Juvenile Criminal Justice System, together with Government Regulation No. 65 of 2015, allows the return of such children to their parents or guardians, or their placement in education, guidance, or social-welfare programmes. This model protects young children from punitive criminalization, but it also creates a normative difficulty when an under-twelve child commits a serious unlawful act, including sexual violence or homicide, because the law provides no meaningful gradation based on the gravity of the act, the child's individual mental capacity, or the victim's need for justice and protection. This article applies normative juridical research using statutory, conceptual, and policy-oriented approaches. It analyses Indonesian child justice law through the doctrine of fault, Jean Piaget's theory of cognitive and moral development, contemporary developmental science, and international child-rights standards. The article argues that chronological age remains indispensable as a protective threshold, but it should not operate as the sole determinant of legal response. A new category of diminished legal responsibility is proposed for children under twelve who are shown, through multidisciplinary assessment, to possess cognitive and moral understanding beyond their biological age. The category should not authorize imprisonment or criminal conviction. Instead, it should enable proportionate, restorative, rehabilitative, and victim-sensitive measures tailored to the child's maturity, risk profile, family environment, and the seriousness of the unlawful act.